The complete mitochondrial genome of Triplophysa alticeps. Issue 1 (1st January 2016) - Wang, Le; Luan, Pei-Xian; Wang, Ping-Ping; Wang, Qiu-Shi; Lu, Jian-Guo
Abstract: The complete mitochondrial genome of Triplophysa alticeps was 16, 569 bp; it contains 13 protein-coding genes, 22 transfer RNA genes, 2 ribosomal RNA genes, and a D-loop. It is a circular molecule with a typical gene arrangement of vertebrate mitochondrial DNA. This study could be provided insights into the evolution of Osteichthyes mitochondrial genomes.